2015
DOI: 10.1186/s12889-015-1811-5
|View full text |Cite
|
Sign up to set email alerts
|

Household practices related to disease transmission between animals and humans in rural Cambodia

Abstract: BackgroundZoonotic diseases are disproportionately affecting poor societies in low-income countries and pose a growing threat to public health and global food security. Rural Cambodian households may face an increased likelihood of exposure to zoonotic diseases as people there live in close association with livestock. The objectives of the study was to identify practices known to influence zoonosis transmission in rural Cambodian households and relate the practices to agro-ecological region, socio-economic pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 34 publications
2
63
2
Order By: Relevance
“…There are no obvious biological reasons for the observed difference in community carriage between sexes, and the explanation could be local gender‐related behaviour leading to transmission between populations. In the current study population, women are often more responsible for the care of poultry and pigs (high level ESCE/K colonized livestock), while men generally take care of more valuable livestock such as ruminants (low level ESCE/K colonized livestock) (Osbjer et al, ). It has been previously shown that close contact with poultry increased community carriage of ESCE in Dutch humans (Huijbers et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are no obvious biological reasons for the observed difference in community carriage between sexes, and the explanation could be local gender‐related behaviour leading to transmission between populations. In the current study population, women are often more responsible for the care of poultry and pigs (high level ESCE/K colonized livestock), while men generally take care of more valuable livestock such as ruminants (low level ESCE/K colonized livestock) (Osbjer et al, ). It has been previously shown that close contact with poultry increased community carriage of ESCE in Dutch humans (Huijbers et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although comparisons across studies should be cautioned due to methodological differences, findings from a household survey of livestockraising practices in rural Cambodia suggest a similar incongruity between knowledge and perceived risk: while two-thirds of households in the study were aware of zoonoses, only 6% of respondents considered disease transmission between livestock and humans to be likely. 55 Interestingly, despite evidence indicating increased risk of Salmonella infection from contact with backyard poultry, a study of backyard poultry owners in Los Angeles, CA, indicated that only one half of owners believed that poultry in urban areas could lead to more illness in humans. 56,57 Past zoonotic disease outbreaks in Yaruquí or educational campaigns in the area may have contributed to the relatively high level of awareness of zoonotic disease transmission observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Such results suggest future actions targeting the entire meat production chain for reduced burden of human Campylobacter infection. Moreover, as previously reported, livestock are mainly produced to generate an income and often sold by households [24]. Thus, efficient Campylobacter control ought to move beyond the households with improvements in hygiene practices targeting also external factors along the meat production chain, such as middlemen, abattoirs and consumers.…”
Section: Discussionmentioning
confidence: 99%
“…The interviews, targeted towards the female head of the household, were carried out in Khmer using a household questionnaire consisting of questions on livestock management, meat consumption and household practices related to zoonosis transmission (Table 1). To enhance consistency between the three regions, the field team was trained in questioning and sampling prior to fieldwork [24]. Each village was visited for two consecutive days.…”
Section: Methodsmentioning
confidence: 99%